2018
DOI: 10.2196/preprints.9885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activity Trackers, Relational Affordances, and Device Ecologies of Fitness Technologies (Preprint)

Abstract: BACKGROUND With the proliferation of activity-tracking devices and other smart tools, more users leverage these technologies to track their physical and fitness-related activities. The research on the benefits (and limitations) of these devices tends to focus on the use of a single tool, leaving out the interactions among multiple technologies, and how these interactions influence the way users perceive affordances of activity trackers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…There is an argument to be made that AI directorial organs may make more informed and consistent decisions than the fallible human, 304 but there is also countervailing expert evidence that supports human supremacy in deciding on qualitative or strategic matters due to the complexity of the human instinct and the visionary nature of forward-looking judgment. 305 There is unlikely to be conclusive 'science' that says AI are superior directorial organs than humans. 306 Indeed, although narrow AI can engage successfully in predictive analytics, namely statistical analysis and the identification of patterns of decision-making, 307 there is no evidence that AI is equipped to handle complex, strategic decision-making that entails the weighing of competing facts and evidence; nor has it been demonstrated that AI can understand the complex trade-offs that are required in board decisions.…”
Section: The Hold Of the Powerful Political Economy Groups On Ideology And Institutional Changementioning
confidence: 99%
“…There is an argument to be made that AI directorial organs may make more informed and consistent decisions than the fallible human, 304 but there is also countervailing expert evidence that supports human supremacy in deciding on qualitative or strategic matters due to the complexity of the human instinct and the visionary nature of forward-looking judgment. 305 There is unlikely to be conclusive 'science' that says AI are superior directorial organs than humans. 306 Indeed, although narrow AI can engage successfully in predictive analytics, namely statistical analysis and the identification of patterns of decision-making, 307 there is no evidence that AI is equipped to handle complex, strategic decision-making that entails the weighing of competing facts and evidence; nor has it been demonstrated that AI can understand the complex trade-offs that are required in board decisions.…”
Section: The Hold Of the Powerful Political Economy Groups On Ideology And Institutional Changementioning
confidence: 99%